PENGARUH INTERVAL WAKTU PEMBERIAN PUPUK ORGANIK CAIR ENVIRO TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS MENTIMUN (Cucumis sativus L.) - Jumini Jumini; Hasinah Hasinah; Armis Armis (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2012)
This study was aimed at determining appropriate time interval of providing liquid organic fertilizer Enviro to growth and yield of two varieties of cucumber and interaction betweenthe time interval and the variety. The experiment was carried out on flood plain of Krueng Lamnyong, Shiah Kuala Sub District, Banda Aceh from November 2008 to January 2009, using a factorial randomized complete block design 4x2 with three replications. Factors studied were time interval of providing liquid organic fertilizer Enviro, consisting of 4 levels ( 5, 7, 9 and 11 days and varieties, consisting of 2 levels (local varieties and Hercules 56). Variables observed were plant height, fruit numbers, fruit length, fruit diameter, and fruit Weights. Results showed that the time interval of providing liquid organic fertilizer Enviro did not affect plant height at age of 10, 20, and 30 days after planting (DAP), the number, length, diameter and weight of cucumber fruits harvested for 4 times. On the other hand, variety exerted significant effects on plant height at age of 10, 20 and 30 DAP, the number, length and weight of fruits, but did not exert a significant effect on fruit diameter. The best growth and length of cucumber fruits were found on varieties Hercules 56, while the number, diameter and weight of fruits of four Time harvest were found on local varieties. There was no significant interaction between time interval and variety on all variables observed.